The Effectiveness of Online Learning in Solubility and Solubility Product Constant Materials on Students’ Analytical Thinking Skills - Leny Heliawati*; Uun Sundari; Anna Permanasari (Jurnal Pendidikan Sains Indonesia, 2021)
Analytical thinking skill is a part of higher order thinking skills. The ability to think analytically is very important for students who want to help solve problems and make decisions that can be applied in learning and life. This study aims to determine the improvement of students’ analytical thinking skills on the material solubility and solubility product which is carried out in online learning during the Covid-19 pandemic. This study uses a pre-experimental design, with the model The One Group Pretest – Posttest. The population of this study was students of class XI IPA SMAIT Insantama Bogor in the even semester of the 2019/2020 school year. The data were collected by using the thinking instrument skill test which was used in the form of an analytical thinking ability essay covering 3 indicators: distinguishing, organizing, and attributing. The results showed the dominance of students’ analytical thinking skills at the beginning of the period with the average majority (44%), and after treatment, increased in the very good category (74%). The N-gain score for the results of increasing students’ thinking skills is 0.70, which is in the high category. This study concludes that online learning in the material of solubility and solubility results proved to be effective in improving students’ analytical thinking skills during the pandemic